Productivity-Weighted Labor-Force Dependency Ratio and its Impact on Projection Analysis of the Czech Population - Xu, Bingyan; Burlakov, Georgi; Krejčová, Nikola, 1974-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2023)
The demographic situation in the Czech Republic is relatively stable, but the population continuing aging problem and the low fertility rates affect the demographic structure of the labor market. This thesis aims to explore whether these observed declining trends in the age and size of the Czech population should be considered as a restrictive factor for the economic development of the country in the long run. Or, they can well be compensated by the enhanced labor productivity as a result of the parallelly observed trends of increasing shares of the population with higher education actively participating in the labor force. The latter conjecture is taken as the main research hypothesis of the thesis. Respectively, it is aligned with the labor economics concepts of demographic transition, human capital, and labor force participation which as presented in the theoretical part all emphasize the importance of education and wide labor force inclusion of the population for the country’s economic development. The results of the descriptive analysis of EUROSTAT macro data for the Czech population in the period 2004-2021 are presented in a special section of the empirical part of the thesis based on which implications are made about the recent trends in the active labor participation share and education structure of the Czech population. Finally, time-series forecasting scenarios are developed based on extrapolation of the historical trends of three key demographic measures. On top of the conventional age-dependency ratio as a measure of the pure physical structural change in population size, also the basic and productivity-weighted labor force dependency ratios are estimated in line with a series of recent research papers on the topic.
Vedoucí práce: Georgi Burlakov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses